(untitled) (Revista Argentina de Musicología, 2021)
Approximately 466km from the obelisk and much further from the present time that the artistic and academic scenarios around tango phenomenon pass through, this musical genre, poetry and dance has been mobilized and (re)produced in the city of Santa Fe throughout the 20th century under socio-cultural contexts different from those of the Buenos Aires city. In this framework, wondering about the women roles, their subversive potential and their artistic contribution in an environment saturated with men enriches, includes and enhances the existing and scarce historical constructions of tango in Santa Fe society. As a consequence, to generate this research with a gender perspective, hemerographic sources [newspaper] and audiovisual records will be analyzed in addition to interviews and a critical review of locally produced histories. In this way, an attempt will be made to enlighten an artistic context little studied and discriminated against, its protagonists, as well as of the weaknesses and problems in the different historical account.